THE FIRST RECORDS OF Limnonectes kohchangae (SMITH, 1922) AND Sylvirana mortenseni (BOULENGER, 1903) FROM PHU QUOC ISLAND, SOUTHERN VIETNAM - Thanh Luan, Nguyen; Quang Ngon, Lam; Van Manh, Le; Van Ha, Hoang; E. M. McCormack, Timothy; Tapley, Benjamin (Journal of Forestry Science and Technology, 2022)
We provide the first detailed records of Limnonectes kohchangae (Smith, 1922) and Sylvirana mortenseni (Boulenger, 1903) for Phu Quoc island, Phu Quoc National Park, Kien Giang province, Southern Vietnam. These records are supported by morphology and molecular data. Sylvirana mortenseni was associated with large streams between 23 – 102 m asl. This species has an adult snout–vent length of 46.0 – 80.9 mm in 3 adult males and 47.7 – 69.2 mm in 3 adult females. Males have large humeral glands and well developed nuptial pads; a lack of oblique, triangular or teardrop-shaped marking posterior to the tympanum; a dark stripe beneath the dorsolateral fold which lacks a strong demarcation between the dark upper surfaces of the flank and the lighter lower surface; and distinct dark marbling on the posterior surfaces of the thighs. Limnonectes kohchangae was associated with stream headwaters and small streams between 34–201 m asl. Individuals from Phu Quoc Island had an adult snout – vent length ranging from 34.3 – 41.8 mm in 9 males and 33.3 – 38.2 mm in 2 females. Dorsum with distinctly elongated tubercles and arranged in rows; a bicoloured tympanum with heavily pigmented upper half; dark spots present on flanks; and a broad band on shank with maximum shank band width > 50% horizontal diameter of eye. This report increases the number of amphibians known to occur on Phu Quoc Island from 14 to 16 species.